2007
DOI: 10.5194/acp-7-1671-2007
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of interannual and seasonal variations of model-simulated tropospheric NO<sub>2</sub> in Asia and comparison with GOME-satellite data

Abstract: Abstract. Systematic analyses of interannual and seasonal variations of tropospheric NO 2 vertical column densities (VCDs) based on GOME satellite data and the regional scale chemical transport model (CTM), Community Multi-scale Air Quality (CMAQ), are presented for the atmosphere over eastern Asia between 1996 and June 2003. A newly developed year-by-year emission inventory (REAS) was used in CMAQ. The horizontal distribution of annual averaged GOME NO 2 VCDs generally agrees well with the CMAQ results. Howev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
66
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(76 citation statements)
references
References 19 publications
(32 reference statements)
10
66
0
Order By: Relevance
“…Indeed, it has been suggested that the REAS emission inventory used in our study for Asia underestimates Asian NO x emissions and trends (Kurokawa et al, 2009;Uno et al, 2007). More precisely, Uno et al …”
Section: Long-range Transport From Asiamentioning
confidence: 98%
“…Indeed, it has been suggested that the REAS emission inventory used in our study for Asia underestimates Asian NO x emissions and trends (Kurokawa et al, 2009;Uno et al, 2007). More precisely, Uno et al …”
Section: Long-range Transport From Asiamentioning
confidence: 98%
“…4.4) (Byun and Schere, 2006) Uno et al (2007) and Itahashi et al (2010). Therefore, here we only describe aspects relevant to this study.…”
Section: Chemical Transport Modelmentioning
confidence: 99%
“…Because of the short lifetime of NO x in the troposphere, satellite NO 2 observations are closely correlated to surface NO x emissions. The tropospheric NO 2 VCD retrieved from satellites has been successfully used to evaluate and quantify the spatial distribution and long-term trends of NO x emissions van der A et al, 2008;Han et al, 2009;Lamsal et al, 2011;Schneider and van der A, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, advances in satellite technology and the development of new instruments and algorithms have allowed for observations of the NO 2 vertical column density (VCD) from space, providing useful information for airquality research (e.g., Richter et al, 2005;van der A et al, 2008;Irie et al, 2009). A global picture of the spatial distribution of the NO 2 VCD is now available because satellite measurements provide global coverage in a very short time (between 1 and 6 days depending on the instrument although more time is needed when cloud cover is present).…”
Section: Introductionmentioning
confidence: 99%